3D limit equilibrium method for rock slope stability analysis using generalised anisotropic material model - Kumar, NS; Ismail, MAM (Slope Stability 2020: Proceedings of the 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
Rock anisotropy is a well-known phenomenon relating to the heterogeneity of rock mass. Nevertheless, its influence in geotechnical design, especially in rock engineering, is often ignored. Slope with certain modes of failure can be evaluated conventionally as well as numerically. For this study, the rock slope assessment was conducted numerically using 2D and 3D limit equilibrium method (LEM) utilising the Slide program by Rocscience. The fundamental roles of the discontinuities present in the study area were evaluated to study their influence on slope stability. Anisotropic material model was incorporated in the LEM analysis to investigate the presence of discontinuities. The measurement of discontinuity orientation in the rock slope by traditional scanline survey is time-consuming and challenging due to accessibility issues. Structure from Motion (SfM) photogrammetry using unmanned aerial vehicle (UAV) allows a quick and cost-effective way to do survey mapping for geotechnical assessment on rock slope compared to terrestrial laser scanner. Dense point cloud is exported to the CloudCompare tool for geological plane extraction. The stability of the rock slope was evaluated using the deterministic 3D and 2D LEM using the geometry of the 3D rock slope system. In this study, the anisotropic material model was utilised to examine the Factor of Safety (FoS) results. Generalised anisotropic material model was used for incorporating the generalised Hoek–Brown criterion (rock mass) and Barton–Bandis criterion (weak joint). The rock mass and shear strength parameter for numerical analysis were determined via destructive and non-destructive tests such as uniaxial compressive strength, Schmidt hardness and joint roughness coefficient estimation using Barton comb. Mean dip/dip direction obtained was used as an input for the value of the anisotropic plane where it causes a weakness in the strength of the rock slope. The results of FoS shows that rock slope without anisotropy model is stable and analysis using anisotropic material model predicts that the slope may fail. 3D slope stability analysis was able to identify the weakest spot easily rather than making an assumption based on the results of 2D slope stability assessment which might represent the whole rock slope. 3D rock slope stability assessment proves to be a very cost-effective method for remedial work whereas in 2D stability assessment, wrong cut-sections may provide inaccurate FoS. This study presents the approach of using anisotropic material model utilising basic rock testing and field observation data to analyse the rock slope stability.
Keywords: anisotropy